Environmental drivers of Culicoides phenology: how important is species-specific variation when determining disease policy? - Kate R Searle; James Barber; Francesca Stubbins; Karien Labuschagne; Simon Carpenter; Adam Butler; Eric Denison; Christopher Sanders; Philip S Mellor; Anthony Wilson; Noel Nelson; Simon Gubbins; et al. (PLoS ONE)
Since 2006, arboviruses transmitted by Culicoides biting midges (Diptera: Ceratopogonidae) have caused significant disruption to ruminant production in northern Europe. The most serious incursions involved strains of bluetongue virus (BTV), which cause bluetongue (BT) disease. To control spread of BTV, movement of susceptible livestock is restricted with economic and animal welfare impacts. The timing of BTV transmission in temperate regions is partly determined by the seasonal presence of adult Culicoides females. Legislative measures therefore allow for the relaxation of ruminant movement restrictions during winter, when nightly light-suction trap catches of Culicoides fall below a threshold (the 'seasonally vector free period': SVFP). We analysed five years of time-series surveillance data from light-suction trapping in the UK to investigate whether significant inter-specific and yearly variation in adult phenology exists, and whether the SVFP is predictable from environmental factors. Because female vector Culicoides are not easily morphologically separated, inter-specific comparisons in phenology were drawn from male populations. We demonstrate significant inter-specific differences in Culicoides adult phenology with the season of Culicoides scoticus approximately eight weeks shorter than Culicoides obsoletus. Species-specific differences in the length of the SVFP were related to host density and local variation in landscape habitat. When the Avaritia Culicoides females were modelled as a group (as utilised in the SFVP), we were unable to detect links between environmental drivers and phenological metrics. We conclude that the current treatment of Avaritia Culicoides as a single group inhibits understanding of environmentally-driven spatial variation in species phenology and hinders the development of models for predicting the SVFP from environmental factors. Culicoides surveillance methods should be adapted to focus on concentrated assessments of species-specific abundance during the start and end of seasonal activity in temperate regions to facilitate refinement of ruminant movement restrictions thereby reducing the impact of Culicoides-borne arboviruses.